2008
DOI: 10.1007/s11669-008-9321-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of Silicon Reactivity in General Galvanizing

Abstract: In general galvanizing Si dissolved from steels destabilizes the C and C 1 phases in the alloy layer of the coating. It also alters the morphology of f crystallites in the alloy layer thereby exposing the d layer to the melt. The incompatibility of the liquid phase and the d phase cause the latter to disintegrate. These changes result in an excessive steel reactivity in general galvanizing. This reactivity can be easily controlled by alloying the Zn bath with metals, such as Ni, if the Si content of the steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In the present study, the chemical potential gradient of Fe and Zn governs the alloy reaction and can provide the basis to explain the fact that the Fe-Zn interdiffusion is markedly retarded on the steel containing 0.44 wt% Si. Su et al and 31) Tang et al 24) calculated the FeZn-Si ternary phase diagram at 450°C and experimentally verified the phase boundaries associated with the various Fe-Zn phases. It was found that the solubility of Fe in liquid Zn decreases significantly with increasing the Si concentration in the liquid, as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the present study, the chemical potential gradient of Fe and Zn governs the alloy reaction and can provide the basis to explain the fact that the Fe-Zn interdiffusion is markedly retarded on the steel containing 0.44 wt% Si. Su et al and 31) Tang et al 24) calculated the FeZn-Si ternary phase diagram at 450°C and experimentally verified the phase boundaries associated with the various Fe-Zn phases. It was found that the solubility of Fe in liquid Zn decreases significantly with increasing the Si concentration in the liquid, as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…7,10,12,24) According to the nucleation mechanism, there are two possible routes to nucleate the ζ phase in the coating. First, the ζ phase can nucleate and grow at the area without or with lower Si contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the silicon content of about 1% (high-silicon steel) the FeSi phase amount becomes significantly greater ( Figure 6) [9]. а -95% Zn, b -98% Zn [9] Foreign studies have also confirmed the existence of an equilibrium state between the liquid, the ζ-phase, and FeSi-phase, which prevents the equilibrium between the liquid phase and the δ-phase [10,11]. This phenomenon destroys the integrity of the coating layers; liquid zinc has the direct contact with the steel base, which accelerates the interdiffusion of iron and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…In the galvanizing industry, the phenomenon is commonly referred to as the Sandelin effect or Si reactivity. [1,2] Adding alloy elements into zinc bath are a reliable effective method to counter the phenomenon. In the primitive galvanizing technology, lead (Pb) was frequently added to the zinc bath to improve the fluidity of molten zinc and the development of spangles at the coating surface.…”
Section: Introductionmentioning
confidence: 99%